2005
DOI: 10.1177/0021998305051807
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Hygrothermally Conditioned Polymer Composites with Voids

Abstract: It is well known that voids and environmental conditions may affect the strength of composite laminates. Despite the fact that voids facilitate moisture absorption, the effect of voids on the composite laminates in the presence of moisture has not been addressed in the literature. Moreover, most of the attention has been focused on composites made of unidirectional carbon-epoxy prepreg tape. This article presents experimental results on the combined effect of voids and moisture in polymer composites. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 22 publications
(52 reference statements)
0
73
0
Order By: Relevance
“…Damage evolution of the aged specimen was primarily caused by the debonding of the fiber/matrix inter-face. Voids could potentially amplify the effects of moisture absorption in the laminate, and introduce high stress concentrations that facilitate the development of microcracks [9]. Moisture absorption accelerates the damage propagation in the composite.…”
Section: Mechanical Testsmentioning
confidence: 99%
See 4 more Smart Citations
“…Damage evolution of the aged specimen was primarily caused by the debonding of the fiber/matrix inter-face. Voids could potentially amplify the effects of moisture absorption in the laminate, and introduce high stress concentrations that facilitate the development of microcracks [9]. Moisture absorption accelerates the damage propagation in the composite.…”
Section: Mechanical Testsmentioning
confidence: 99%
“…A compressive test is principally driven by the behavior of the resin and the fiber/matrix interfaces, especially in hygrothermal aging conditions. Costa et al [9] indicated that the water absorbed by the laminates causes either reversible or irreversible plasticization of the matrix. Combined with the temperature effects, these factors may cause significant changes in the matrix toughness, affecting the laminate strength.…”
Section: Compressive Strength Testmentioning
confidence: 99%
See 3 more Smart Citations